Influence of helicobacter pylori on composition and function of gastric microbiota in patients with chronic non-atrophic gastritis - Fan Zhao; Linlin Yan; Pengfei Wang; Ke Zhang; Shoukui Hu (Heliyon, 2024)
Objective: Helicobacter pylori (H. pylori) plays a major role in causing and advancing gastrointestinal illnesses. Our aim is to analyze the unique makeup and functional changes in the gastric microbiota of patients with chronic non-atrophic gastritis (CNAG), regardless of the presence of H. pylori, and to determine the potential signaling pathways. Methods: We performed metagenomic sequencing on gastric mucosa samples collected from 17 individuals with non-atrophic gastritis, comprising 6 cases were infected with H. pylori (H. pylori-infected case group) and 11 cases without (control group). The species composition was evaluated with DIAMOND software, and functional enrichment was assessed utilizing the Kyoto Encyclopedia of Genes and Genomes (KEGG) database. We analyzed antibiotic resistance patterns using the Comprehensive Antibiotic Resistance Database as a reference (CARD). Results: The presence of H. pylori colonization in CNAG patients was associated with increased diversity in the gastric microbiota. The Phylum Firmicutes was found to be less prevalent, while the Phylum Proteobacteria showed an increase. Functionally, pathways associated with metabolic pathways, including vitamins, auxiliaries, amino acid residue, carbon hydrate, and metabolic energy pathways, were enriched in CNAG patients with H. pylori infection. Additionally, antibiotic resistance genes correlated with antibiotic efflux pump were enriched. Conclusions: From a holistic genomic perspective, our findings offer fresh perspectives into the gastric microbiome among CNAG patients carrying H. pylori, which is valuable for future research on CNAG.